HIL testovaní bateriového systému studentské formule - Přikryl, Matouš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
Práce se zabývá hardware-in-the-loop testováním bateriového systému studentské formule. Na začátku práce je provedena rešerše testování bateriových systémů. Zaměření je kladeno na hardware a software, který k tomuto účelu můžeme využít. V druhé části práce je popsáno rozvržení připojení BMS studentské formule k testovací soustavě a její následné testování. Využito bylo vlastních modelů částí formule a kód napsaný specificky pro účely této práce. Závěrečná část práce popisuje vyhodnocení testů a validaci modelů simulovaných částí.

The thesis covers the topic of hardware-in-loop testing of the battery management system of student formula. The beginning of the thesis contains a literature review on the topic of battery management systems testing with an emphasis on the hardware and software that can be used for this purpose. In the second part of the thesis, the layout of the BMS connection to the test rig and its subsequent testing is described. Custom models of the formula parts and code written specifically for this thesis were used for the testing of the BMS. The final part contains test analysis and validation of the models of the simulated parts.
HIL testing of student formula battery management system
Keywords: Hardware-in-the-loop; HIL; Bateriový systém; BMS; Testování; Formule Student; Validace; dSPACE; Hardware-in-the-loop; HIL; Battery management system; BMS; Testing; Fomula Student; Validation; dSPACE